CXC Chemokines in the Pathogenesis of Pulmonary Disease and Pharmacological Relevance - Kayode Komolafe; Maricica Pacurari (International Journal of Inflammation)
Chemokines and their receptors play important roles in the pathophysiology of many diseases by regulating the cellular migration of major inflammatory and immune players. The CXC motif chemokine subfamily is the second largest family, and it is further subdivided into ELR motif CXC (ELR+) and non-ELR motif (ELR-) CXC chemokines, which are effective chemoattractants for neutrophils and lymphocytes/monocytes, respectively. These chemokines and their receptors are expected to have a significant impact on a wide range of lung diseases, many of which have inflammatory or immunological underpinnings. As a result, manipulations of this subfamily of chemokines and their receptors using small molecular agents and other means have been explored for potential therapeutic benefit in the setting of several lung pathologies. Furthermore, encouraging preclinical data has necessitated the progression of a few of these drugs into clinical trials in order to make the most effective use of interventions in the development of viable targeted therapeutics. The current review presents the understanding of the roles of CXC ligands (CXCLs) and their cognate receptors (CXCRs) in the pathogenesis of several lung diseases such as allergic rhinitis, COPD, lung fibrosis, lung cancer, pneumonia, and tuberculosis. The potential therapeutic benefits of pharmacological or other CXCL/CXCR axis manipulations are also discussed.